2014
DOI: 10.1084/jem.20140212
|View full text |Cite
|
Sign up to set email alerts
|

Nfil3 is crucial for development of innate lymphoid cells and host protection against intestinal pathogens

Abstract: Nfil3 is critical for normal development of innate lymphoid cell (ILC) progenitors. Nfil3-deficient mice have severely reduced lung and visceral adipose tissue ILC2s and gut-associated ILC3s, and compromised innate immunity to acute bacterial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
185
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(197 citation statements)
references
References 64 publications
11
185
0
1
Order By: Relevance
“…[42][43][44] Nfil3-deficient mice display a severe defect in NK-cell development, 45,46 in addition to impaired development of CD8 1 and CD103 1 conventional DC subsets, B cells, and other innate lymphoid subsets. 44,[47][48][49] Reduced GATA-2-mediated induction of NFIL-3 could thus contribute to DC, B-cell, and NK-cell cytopenias observed in humans with GATA-2 haploinsufficiency, as suggested by our findings of reduced NK-cell output from Lin 2 cell progenitors in patients with GATA2 mutation. Interestingly, CMV infection bypasses the requirement for Nfil3 in mouse NK-cell development, supporting generation of long-lived, adaptive NK cells.…”
Section: Discussionmentioning
confidence: 56%
“…[42][43][44] Nfil3-deficient mice display a severe defect in NK-cell development, 45,46 in addition to impaired development of CD8 1 and CD103 1 conventional DC subsets, B cells, and other innate lymphoid subsets. 44,[47][48][49] Reduced GATA-2-mediated induction of NFIL-3 could thus contribute to DC, B-cell, and NK-cell cytopenias observed in humans with GATA-2 haploinsufficiency, as suggested by our findings of reduced NK-cell output from Lin 2 cell progenitors in patients with GATA2 mutation. Interestingly, CMV infection bypasses the requirement for Nfil3 in mouse NK-cell development, supporting generation of long-lived, adaptive NK cells.…”
Section: Discussionmentioning
confidence: 56%
“…They require RORγt TF and, as recently suggested, may also require E4BP4 TF for their development. They reside in MALT and in secondary lymphoid organs, provide host defenses against extracellular pathogens, and contribute to tissue remodeling [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study revealed that Nfil3 was only required in early progenitor cells and that deletion at the NKP stage (when NKp46 is first expressed) or in mature NK cells surprisingly did not impact total NK cell numbers, function, or response against viral infection (Firth et al 2013). Consistent with this finding, CLP numbers are normal in the Nfil3-deficient mice, and numbers begin to decline as NKPs transition to the iNK stage (Gascoyne et al 2009;Geiger et al 2014). Nfil3 is expressed as early as the CLP stage (and possibly earlier) where it promotes NK cell lineage commitment by directly regulating the expression of Eomes and Id2 , and thus, Id2 overexpression could rescue NK cell development in the setting of Nfil3-deficiency (Gascoyne et al 2009;Male et al 2014).…”
Section: Generation Of An Nk Cell From a Common Lymphoid Progenitormentioning
confidence: 83%